Historyzm wobec starożytności w dziełach J. J. Winckelmanna, W. von Humboldta i F. Schlegla. Próba rekonstrukcji i zarys polskiej recepcji - Junkiert, Maciej (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The second half of the XVIIIth century contribute to radical change of cultural relationship with past. Historicism, understand as a common method of conceptualization of human inventions, appeared not only in historiography, but also marked his presence in literature, philosophy, architecture and art. The aim of this article is to explore some of the outlooks on connection between historicism and the classical antiquity in the works of Winckelmann, Humboldt and Schlegel, important German thinkers with significant reception in Polish literature and culture.
Keywords: Hellenism; history of Greece; Winckelmann; Schlegel; Humboldt